Effects of Multiple Metal Resistant Bacterias on Antioxidants of Pleurotus ostreatus in Metal-Polluted Soil - Wu, Bo; Qin, Chui-Xin; Cui, Bo-Miao; Zhao, Kun; Xu, Heng (Asian Journal of Chemistry, 2014)
In this study, the effects of two heavy-metal-mobilizing bacterias CT1 and WK1 on fruiting body growth, Cd and Pb accumulation, lipid peroxidation, protein content and antioxidant system in Pleurotus ostreatus were assessed in Cd and Pb contaminated soil. Pot experiments showed that inoculation with CT1 and WK1 not only partly promoted the growth of P. ostreatus, but also enhanced the accumulation of Cd and Pb compared to control, respectively. Moreover, protein level in P. ostreatus inoculation with CT1 and WK1 displayed an increase. Besides, a significant decrease in malondialdehyde content suggested that both bacterial strains can alleviate lipid peroxidation in P. ostreatus. Antioxidant enzyme superoxide dismutase, peroxidases and catalase (CAT) activities of P. ostreatus also showed obviously decrease by inoculation with CT1 and WK1. Therefore, the present work suggests that heavy metal-solubilizing bacterias can reduce the toxicity of metals to fruiting body and then alleviate heavy metals-inducing oxidative stress in P. ostreatus.